Charactirestics of vitamin D level in patients with atopic dermatitis - Garibeh , E.; Bondаr S.А.; Tokarchuk , N.I.; Vyzgha, Y.V. (Medicni Perspektivi, 2022)
The peculiarity of the skin is that it acts not only as a place of synthesis of vitamin D, but also as an organ targeted for its biologically active form. The aim of our study was to analyze the level of vitamin D in patients with atopic dermatitis. There were examined 48 people aged between 18 to 55 years; they are residents of Vinnytsia and Vinnytsia region. Serum levels of vitamin D, total IgE and eosinophilic cationic protein (ECP) were determined in the subjects. The average level of vitamin D in the serum of patients with atopic dermatitis was 19.2 [11.3-25.4] ng/ml, which corresponded to a deficiency. Among those surveyed, vitamin D deficiency was found in 68.4±4.7% (n=26) while vitamin D insufficiency in 31.6±4.5% (n=12). The severe course of the disease prevailed among patients aged 18-40 years (63.33±8.79) % more than in the age group of 41 years and older, (36.67±8.8%, p<0.05; OR=2.98, S=0.53, 95% SI:1.04-8.52). The proportion of people with vitamin D deficiency and moderate severity of atopic dermatitis was 62.5% (n=10) with a median level of 14 [8.3–19] ng/ml, and patients with severe atopic dermatitis made up 90.9% (n=20) (χ²=4.6; p=0.023), in which the median level of vitamin D was 14 [8.3-19] ng/ml. Serum vitamin D levels were in the zone of deficiency in patients with moderate and severe atopic dermatitis. Vitamin D deficiency was significantly more common in the group of patients with elevated levels of allergic inflammation markers. A positive correlation of medium strength between the level of vitamin D and ECP in the serum of patients with atopic dermatitis (rs=0.53, p<0.001), was revealed.